PENGEMBANGAN BAHAN AJAR BERBASIS METODE KONTRUKTIVISME UNTUK MENINGKATKAN KEMAMPUAN BERBICARA SISWA DI LEMBAGA BAHASA ARAB DAN INGGRIS (LBAI) PP. MAMBA’UL MA’ARIF DENANYAR JOMBANG - Ichsan Nur Qolbi; Amrini Shofiyani (Institut Pendidikan Tapanuli Selatan, 2021)
In the world of education, the development of language is currently very fast in the world of education, the language used is not only the national language of the country itself, but many countries have included foreign languages ​​in teaching and learning activities.Given the many things that need to be learned in foreign languages, especially Arabic Language, to improvestudent interest in learning and improve the quality of student learning outcomes, the researchers developed the existing textbooks into teaching materials based on constructivism methods.